Experimental Investigation on the Cleaning Effect and Influence Rule of Hydrogen Peroxide–Acetic Acid on Lead–Bismuth Eutectic Alloy - Huang, Xi; Pang, Bo; Zhou, Xuelong; Yin, Yuan (Frontiers in Energy Research, 2021)
During the refueling process of lead–bismuth eutectic (LBE)–cooled fast reactors, lead–bismuth alloy can easily adhere to the surface of the fuel rod clads when spent fuel assemblies are unloaded from the reactor core. For some designs, the lead–bismuth alloy attached on the spent fuel rods will be cleaned via physical or/and chemical methods prior to their transportation, storage, and reprocessing. In this article, the cleaning effect of a washing lotion composed of hydrogen peroxide (H2O2) aqueous solution and concentrated acetic acid (CH3COOH) as the main components on LBE was experimentally investigated. By adjusting the composition ratio of the washing lotion and the reaction temperature, the law of their influence on the cleaning effect of LBE was determined. The optimal washing lotion composed of 30 Vol% hydrogen peroxide aqueous solution as oxidant, 40 Vol% concentrated acetic acid as acid, and 30 Vol% ultrapure water as the solvent was proposed based on experimental investigations. The optimal working temperature range was also obtained. The reaction intermediate product was characterized with the XRD analysis in order to understand the reaction mechanism. The composition of the released gas (even in a slight amount) was also analyzed with gas chromatography. The hydrogen concentration in the released gas was found to be lower than the detection limit of gas chromatography (10 ppm). Since the explosion limits of hydrogen at atmospheric pressure are between 3.95 and 75.73 Vol%, the risk of possible hydrogen explosion is concluded to be extremely low. Therefore, no special treatment of the released gas is required even in a large-scale industrial platform. Furthermore, corrosion effect of the washing lotion on austenitic stainless steel components was tested as well and found to be negligibly small. The relative mass loss of the thin-walled stainless steel samples immersed in the washing lotion was found to be less than 0.5% after an experimental duration of 144 h, which facilitates sufficient cleaning time in future industrial applications.